2021
DOI: 10.5513/jcea01/22.1.3024
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and sensory evaluation of early ripening peach and nectarine varieties

Abstract: The present study was carried out to determine some physicochemical, composition and sensory attributes of earlyripening peach varieties: "Filina" (peach), "Gergana" (nectarine), and "Ufo-4" (flat peach). Fruit weight, shape and size, as well as color and firmness were evaluated. Image analysis was used to describe properties such as length, width, thickness, etc. Skin hue ranged from 33.45±10.70 to 42.75±29.87. Dry matter (%), ash content (%), total soluble solids, pH, titratable acidity, total sugar content,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
(24 reference statements)
0
2
1
Order By: Relevance
“…The energy value found in this study was approximately 4 kcal/kg which is slightly a little higher than the values reported by Grigelmo-Miguel et al ( 56 ) (3.5–3.7 kcal/g); differences could be associated with the high sugar content explained by the °Brix values and total sugar content of 13.84 °Brix and 60%, respectively. These results were higher than the values reported for early ripening of peach and varieties of nectarines such as “Filina,” “Ufo-4,” and “Gergana” from Eastern Europe ( 58 ) and peaches harvested in the north of China ( 59 , 60 ). On the other hand, the values found in this study were less than those reported by the study mentioned in the reference ( 55 ) for peaches from northern Spain, showing that there are many factors affecting their physicochemical parameters, such as the stage of maturity at picking, storage conditions, origin, or the physiological effects caused by seasonal conditions in the northern hemisphere, which are absent in Colombia.…”
Section: Resultscontrasting
confidence: 69%
“…The energy value found in this study was approximately 4 kcal/kg which is slightly a little higher than the values reported by Grigelmo-Miguel et al ( 56 ) (3.5–3.7 kcal/g); differences could be associated with the high sugar content explained by the °Brix values and total sugar content of 13.84 °Brix and 60%, respectively. These results were higher than the values reported for early ripening of peach and varieties of nectarines such as “Filina,” “Ufo-4,” and “Gergana” from Eastern Europe ( 58 ) and peaches harvested in the north of China ( 59 , 60 ). On the other hand, the values found in this study were less than those reported by the study mentioned in the reference ( 55 ) for peaches from northern Spain, showing that there are many factors affecting their physicochemical parameters, such as the stage of maturity at picking, storage conditions, origin, or the physiological effects caused by seasonal conditions in the northern hemisphere, which are absent in Colombia.…”
Section: Resultscontrasting
confidence: 69%
“…Thirty peaches/nectarines of each variety were divided into three groups and were positioned in three orientations and photographed with a Nikon D5600 digital SLR camera as described by Popova et al (2021). The obtained coloured .tiff images were processed and analysed with ImageJ software to determine the length, width, and thickness of the selected peach/stone (Figure 1).…”
Section: Fruit and Stone Biometrymentioning
confidence: 99%
“…The highest values for brightness can be found in the RFF formulation, whereas "b" (≥19.48) color parameters hint for a yellow shade. The L values of formulations CFF and RFF are highly influenced by the peach flesh color (65.13 ± 6.33) [44]. The "h" value ranging from 74.54 ± 0.89 (RLF) to 81.50 ± 1.44 (RFF) also indicates a predominating yellow color of the formulations.…”
Section: Cielab Color Spectra Of the Nectarine-enriched Puddingsmentioning
confidence: 99%